Manajemen Program Hybrid Learning dalam Penguatan Akhlak Di MI Baitul Huda Klampisan Semarang - Mohammad Hirzi An-naeda; Nur Asiyah; Ruruh Sarasati (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze the management of the hybrid learning program in strengthening students' morals at MI Baitul Huda Klampisan Semarang. The focus of the study includes the planning, organizing, implementation, and controlling processes of the hybrid learning program, as well as the supporting factors, inhibiting factors, and their implications for strengthening students' morals. This study is qualitative research employing a case study approach. The research subjects consisted of the principal, teachers, and students selected using a purposive sampling technique. Data were collected through semi-structured interviews, participant observation, and documentation studies. Data validity was tested through source triangulation, technique triangulation, and member checking. Data analysis employed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the management of the hybrid learning program has been implemented through the integration of learning technology and the religious culture of the madrasah. At the planning stage, the madrasah developed technology-based learning tools combined with religious habituation programs. Organizing was carried out through a clear division of responsibilities among the principal, teachers, students, and parents. The implementation of the program utilized digital media such as projectors, instructional videos, Quizizz, and WhatsApp, combined with religious activities including the recitation of Asmaul Husna, congregational Dhuha prayer, and a culture of greeting. Controlling was conducted through the evaluation of academic aspects and students' moral development. Supporting factors of the program include teacher readiness, principal support, learning facilities, religious culture, and parental involvement, whereas inhibiting factors include limitations in internet connectivity, digital devices, and students' technological literacy. This study concludes that systematically managed hybrid learning is capable of supporting the strengthening of students' morals through the integration of technology and religious habituation. These findings contribute to the development of technology-based Islamic education management and serve as a reference for madrasahs in developing digital learning oriented toward the formation of akhlakul karimah. Keywords: hybrid learning; management; character strengthening; islamic education; madrasah ibtidaiyah Abstrak: Penelitian ini bertujuan untuk menganalisis manajemen program hybrid learning dalam penguatan akhlak siswa di MI Baitul Huda Klampisan Semarang. Fokus penelitian meliputi proses perencanaan, pengorganisasian, pelaksanaan, dan pengendalian program hybrid learning, serta faktor pendukung, faktor penghambat, dan implikasinya terhadap penguatan akhlak peserta didik. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Subjek penelitian terdiri atas kepala madrasah, guru, dan siswa yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui wawancara semi-terstruktur, observasi partisipatif, dan studi dokumentasi. Keabsahan data diuji melalui triangulasi sumber, triangulasi teknik, dan member checking. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa manajemen program hybrid learning telah dilaksanakan melalui integrasi teknologi pembelajaran dan budaya religius madrasah. Pada tahap perencanaan, madrasah mengembangkan perangkat pembelajaran berbasis teknologi yang dipadukan dengan program pembiasaan keagamaan. Pengorganisasian dilakukan melalui pembagian tugas yang jelas antara kepala madrasah, guru, siswa, dan orang tua. Pelaksanaan program memanfaatkan media digital seperti proyektor, video pembelajaran, Quizizz, dan WhatsApp yang dikombinasikan dengan kegiatan religius berupa pembacaan Asmaul Husna, shalat dhuha berjamaah, dan budaya salam. Pengendalian dilakukan melalui evaluasi terhadap aspek akademik dan perkembangan akhlak siswa. Faktor pendukung program meliputi kesiapan guru, dukungan kepala madrasah, fasilitas pembelajaran, budaya religius, dan keterlibatan orang tua, sedangkan faktor penghambat mencakup keterbatasan jaringan internet, perangkat digital, dan literasi teknologi siswa. Penelitian ini menyimpulkan bahwa hybrid learning yang dikelola secara sistematis mampu mendukung penguatan akhlak siswa melalui integrasi teknologi dan pembiasaan religius. Temuan ini berkontribusi terhadap pengembangan manajemen pendidikan Islam berbasis teknologi serta menjadi referensi bagi madrasah dalam mengembangkan pembelajaran digital yang berorientasi pada pembentukan akhlakul karimah. Kata Kunci: hybrid learning, manajemen pendidikan, penguatan akhlak, pendidikan Islam, madrasah ibtidaiyah.